2017
DOI: 10.1177/1535370217737983
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective effects of orientin on oxygen-glucose deprivation/reperfusion-induced cell injury in primary culture of rat cortical neurons

Abstract: Orientin (luteolin-8-C-glucoside) is a phenolic compound found abundantly in millet, juice, and peel of passion fruit and has been shown to have antioxidant properties. In the present study, we explored the effects of orientin on oxygen-glucose deprivation/reperfusion (OGD/RP)-induced cell injury in primary culture of rat cortical neurons using an in vitro model of neonatal ischemic brain injury. The reduced cell viability and elevated lactate dehydrogenase leakage were observed after OGD/RP exposure, which we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The Erk1/2 signaling pathway has a close relationship with neuronal cells differentiation and proliferation; however, previous reports exhibited controversial observations about the role of Erk1/2 in the process of neuroprotection. Studies from Gong et al (2014) and Tian et al (2018) showed that activation of Erk1/2 after OGD or OGD/PR was observed characterized by increased expression of p-ERK1/2. In contrast, some studies demonstrated that Erk1/2 activation contributed to the protective effects of some neuroprotectants.…”
Section: Discussionmentioning
confidence: 99%
“…The Erk1/2 signaling pathway has a close relationship with neuronal cells differentiation and proliferation; however, previous reports exhibited controversial observations about the role of Erk1/2 in the process of neuroprotection. Studies from Gong et al (2014) and Tian et al (2018) showed that activation of Erk1/2 after OGD or OGD/PR was observed characterized by increased expression of p-ERK1/2. In contrast, some studies demonstrated that Erk1/2 activation contributed to the protective effects of some neuroprotectants.…”
Section: Discussionmentioning
confidence: 99%
“…Both enzyme activities, XO and NOX, play a critical role in RONS generation during intense exercise (Morales-Alamo and Calbet, 2014 ) and ischemia/reperfusion events (Berry and Hare, 2004 ). Luteolin mitigates ischemia/reperfusion damage in cell cultures (Tian et al, 2018 ) and animals (Karakaş et al, 2014 ; Hong et al, 2017 ; Liu et al, 2017 ; Luo et al, 2017 ; Du et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, JNK inhibitor SP600125 and ERK1/2 inhibitor PD98059 ameliorated OGD/RP-induced cell death and ROS generation. Further, orientin failed to protect cortical neurons with the JNK activator anisomycin or with the ERK1/2 activator FGF-2 [6], showing that the neuroprotective effects of orientin against OGD/RP-induced damage depend on down-regulation of JNK and ERK1/2 signaling pathways [6]. In a model of OGD/R injury in a primary co-culture of rat cortical capillary endothelial cells, astrocytes and neurons to allow simultaneous observations in the same system, it was found that pretreatment with Ginkgo biloba extract or Ginkgolide B increased neuronal viability, ameliorated cell injury, and inhibited cellular apoptotic rate through Bcl-2 and Bcl-2-associated X protein (Bax) expression [7].…”
Section: Neuroprotective Agents Tested In Himentioning
confidence: 99%
“…Hypoxic-ischemic (HI) brain injury is mainly characterized by decreasing O2 concentration and blood flow, which lead to an inefficient supply of nutrients to the brain. This pathophysiological conditions lead to cell death by energy depletion and increased free radical generation [4], as it is observed in perinatal asphyxia (PA) and ischemic-stroke (IS) [5][6][7]. PA and IS represent one of the main causes of mortality and morbidity in children and adults worldwide [8,9].…”
Section: Introductionmentioning
confidence: 99%